Prodromus of a fern flora for Bolivia. XVI. Salviniaceae - Kessler, Michael; Smith, Alan R. (Phytotaxa, 2017)
We provide a synopsis to the family Salviniaceae in Bolivia, including two species each in the genera Azolla and Salvinia. Despite their low species richness, these aquatic plants are some of the ecologically and economically most important ferns in Bolivia.